2016
DOI: 10.1002/slct.201600006
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylate Coordination Assisted Aggregation for Quasi‐Tetrahedral and Partial‐Dicubane [Cu4] Coordination Clusters

Abstract: The reaction of three copper(II) carboxylate (R = Me, Ph and H in RCO2−) salts in MeOH with H3L resulted three [Cu4] aggregates: [Cu4(μ4‐O)(μ‐H2L)2(μ1,3‐O2CCH3)4] (1), [Cu4(μ4‐O)(μ‐H2L)2(μ1,3‐O2CPh)(PhCO2)3]⋅H2O (2⋅H2O), and [Cu4(μ3‐OH)2(μ‐H2L)2(μ1,1‐HCO2)2(HCO2)2]⋅2H2O (3⋅2H2O). Three different carboxylate groups showing varying coordination modes were responsible for the self‐aggregation of two ligand bound [Cu2(H2L)]3+ units. The [Cu4O] and [Cu4(OH)2] cores were generated from water‐derived oxido and hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…It is also worth mentioning that supramolecular chemists usually analyze the intermolecular interactions in X‐ray structures that are shorter than the sum of the van der Waals radii; longer interactions in the crystal structures are not generally investigated. Clearly, this is a relatively simplistic view of crystal packing, because interactions slightly longer than the van der Waals radii also have an impact . Taking this into account, in this theoretical study we wish to exemplify the contribution of the long‐range interactions in C–H/π bonded assemblies retrieved from the solid‐state structure of [Ni II ( 1 ) 2 ] reported herein.…”
Section: Resultsmentioning
confidence: 99%
“…It is also worth mentioning that supramolecular chemists usually analyze the intermolecular interactions in X‐ray structures that are shorter than the sum of the van der Waals radii; longer interactions in the crystal structures are not generally investigated. Clearly, this is a relatively simplistic view of crystal packing, because interactions slightly longer than the van der Waals radii also have an impact . Taking this into account, in this theoretical study we wish to exemplify the contribution of the long‐range interactions in C–H/π bonded assemblies retrieved from the solid‐state structure of [Ni II ( 1 ) 2 ] reported herein.…”
Section: Resultsmentioning
confidence: 99%
“…This shifting of the imine stretching frequency value to lower wavenumber in complex 1 was due to the donation of lone-pair electrons from ligand imine nitrogen atom to the vacant d-orbital of the Cu(II) ion. 3,13,75,93 The Cu 2+ -bound phenoxido oxygen stretching frequency n (Cu-O/ring stretch) appeared as a weak peak at 861 cm À1 . 94 Electronic spectra of ligand H 2 L and complex 1 displayed several representative bands in the 200-800 nm range in MeCN solution.…”
Section: Synthetic Methodology and Spectroscopic Characterizationmentioning
confidence: 99%
“…The red spots in the graphical plot specified shorter contacts while the white areas highlighted contacts around the van der Waals distance, and the blue color regions indicated longer contacts. d norm = {( d i − r i vdw )/ r i vdw } + {( d e – r e vdw )/ r e vdw }where d i and d e represent the distance between the surface and the nearest internal atom and external atom, respectively, whereas r vdW i and r vdW e are the van der Waals radii of the nearest internal atom to the surface and external atom to the surface, respectively. 75,76 One more important property of curvedness was also evaluated based on the local curvature of the surfaces of complex 1 . A 2D fingerprint plot was also generated to obtain the unique visualization of various intermolecular interactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…† The existence of domain peaks in L$Eu and L$Tb at 2q ¼ 24.91 and 23.70 with d-spacing values of 3.57 and 3.75Å, respectively, was in agreement with the presence of intermolecular p/p stacking interactions in those CPs. 35,36 The L$Eu and L$Tb nanosheets were prepared by liquid exfoliation of their corresponding bulk powder through a topdown sonication assisted strategy, where the bulk layered materials cleaved into few-layered 2D nanosheets (Scheme 1). It was found that chloroform-tetrahydrofuran (1 : 1, v/v) and acetonitrile are ideal solvent systems for the exfoliation of L$Eu and L$Tb bulk powder among the wide range of solvents with different polarities that were tested.…”
Section: Synthesis and Characterization Of L$eu And L$tb Coordinationmentioning
confidence: 99%